Effect of Carbonate Precipitant on the Microstructure and Electrochemical Properties of LiNi0.5Mn1.5O4 Cathodes. Issue 9 (6th June 2018) - Li, Ying; Shi, Lu; Zhou, Yu; Yang, Yang; Mou, Jirong; Hou, Xianhua; Lin, Dunmin; Lam, Kwok-ho
Abstract : Spinel LiNi0.5 Mn1.5 O4 cathode materials with Fd3m space group were prepared using the co-precipitation method via adjusting the amount of Na2 CO3 precipitant. X-ray diffraction and Rietveld refinement revealed that the impurity phase was effectively inhibited after the addition of more amount of Na2 CO3 . All samples, including the pristine LiNi0.5 Mn1.5 O4 sample and that prepared with different extra amounts of Na2 CO3, exhibited uniform polyhedron morphology and their average grain sizes increased with the amount of Na2 CO3 . After adding 5% more Na2 CO3, the average grain size of the sample was larger than 500 nm. When compared to other samples, the amount of impurity phase was minimum in the sample prepared with 5% more Na2 CO3 . Due to the impurity suppression, the LiNi0.5 Mn1.5 O4 sample prepared with 5% more Na2 CO3 exhibited superior electrochemical performance for Li-ion batteries, showing initial discharge capacities of 125.4 mA h g −1 and 126.1 mA h g −1, and high capacity retentions of 90.7% and 87.6% after 200 cycles at 0.1 C and 0.5 C, respectively. It also exhibited the lowest intrinsic resistance and best Li + diffusion kinetics among all the samples deduced from electrochemical impedance spectroscopy.